Autumn fertization of deferred rangeland in shallow soils (Semiárida, 2020)
Winter forage deficit is a recurrent issue in rangelands of southern Brazil, generating nutritional deficiencies to herbivores kept in such conditions, being more decisive in shallow soils. We studied 12 combinations of fertilization and liming related to autumn grazing deferment of rangeland on shallow basaltic soil in order to accumulate forage for use in winter. No significant differences were (P
Keywords: Bare soil; forage deficit; productive types; shallow basaltic soils